Chosen ciphertext secure fuzzy identity based encryption without ROM - Fang, Li-ming; Wang, Jian-dong; Ren, Yong-jun; Xia, Jin-yue; Bian, Shi-zhu (Shanghai jiao tong da xue xue bao, 2008)
Two new constructions of chosen-ciphertext secure fuzzy identity-based encryption (fuzzy-IBE) schemes without random oracle are proposed. The first scheme combines the modification of chosen-plaintext secure Sahai and Waters’ “large universe” construction and authenticated symmetric encryption, and uses consistency checking to handle with ill-formed ciphertexts to achieve chosen-ciphertext security in the selective ID model. The second scheme improves the efficiency of first scheme by eliminating consistency checking. This improved scheme is more efficient than existing chosen-ciphertext secure fuzzy-IBE scheme in the standard model.